Analysis Of The Law On The Authority Of The House Of Representatives (Dpr) On The Removal Of Constitutional Court Judges In Indonesia (The Case Of The Removal Of Judge Aswanto) - Siambaton, Rindi Antika; Irwansyah, Irwansyah (UNIVERSITAS PAKUAN, 2022)
This research focuses on analyzing the authority of the Indonesian House of Representatives (DPR) 's authority in dismissing Constitutional Court judges, particularly in the case of Judge Aswanto. The research methodology used is normative legal research, utilizing library research and the statute approach, and analyzed through juridical-normative analysis. Based on your research, you have found that the DPR's authority in dismissing Constitutional Court judges contradicts the provisions stated in Article 24 Paragraph (1) of the 1945 Constitution and Article 23 of the Constitutional Court Law. Furthermore, you discovered that in the case of Judge Aswanto's dismissal, the Constitutional Court ruled that the DPR had violated the law by not following the correct procedures established by the law. From these findings, you conclude that the DPR's authority in dismissing Constitutional Court judges should be conducted according to the procedures set forth in the law. Failure to adhere to these procedures can be considered a violation of the law and can have detrimental consequences for the parties involved. To prevent the abuse of power and violations of individual rights guaranteed by the constitution, you emphasize the importance of strict law enforcement and supervision of the DPR's authority in dismissing judges of the Constitutional Court. Overall, your research highlights the need for adherence to legal procedures and the significance of upholding the rule of law in the context of the DPR's authority in dismissing judges of the Constitutional Court.